Analysis of student's mathematic numeration ability Based on cognitive level of materials cube and beam - Napsiyah, Napsiyah; Nurmaningsih, Nurmaningsih; Haryadi, Rahman (Universitas Mercu Buana Yogyakarta, 2023)
21st century skills require students to be able to keep up with the times that are full of challenges. One of the requirements to realize 21st century skills is the literacy ability of students. One of the literacy skills that students must possess is numeracy. This type of research is qualitative where the method used is descriptive method. The form of research used in this research is case study research. The subjects of this study were students of class VIII B SMP Negeri 02 Seponti consisting of 19 students who had received cube and block material. The research was conducted on Mey 25 , 2022. The steps used in this research are: the implementation stage, the preparation stage and the final stage. The purpose of this study was to determine the Mathematical Numeration Ability based on the Student's Cognitive Level in Class VIII Cubes and Blocks at SMP N 2 Seponti. Instruments in this study were tests and interviews. The results showed that only 10% of students in class VIII B SMP N 2 Seponti had high numeracy skills, 53% had moderate abilities and 37% students had low abilities .